Evaluation of the first nutritional psychiatry and psychosomatics outpatient clinic: Protocol for a prospective study of an individualized biopsychosocial therapy approach - Sabrina Mörkl; Anna Ramirez-Obermayer; Birgit DelFabro; Sonja Lackner; Sandra Holasek; Julia Traub; Katharina Größbacher; Andreas Brandstätter; Marilena Wilding; Jolana Wagner-Skacel (PLoS ONE, 2026)
Background Psychiatric and psychosomatic conditions are prevalent, disabling, and frequently resistant to standard treatments. Nutrition-focused care represents an emerging integrative approach, but clinical evidence remains scarce. The outpatient department for Nutritional Psychiatry and Nutritional Psychosomatics (NP) at the Medical University of Graz was established as a pilot project, offering add-on therapy with targeted nutritional counseling, nutrient substitution and supplementation, and interventions aiming to improve the gut–brain axis. Methods This prospective, monocentric, observational study will include approximately 84 new patients aged 18–65 over a 12-month period. Participants will complete online questionnaires at baseline and every 3 months, while routine blood samples will assess inflammatory and metabolic markers. The primary outcome is change in perceived stress, measured by the Perceived Stress Scale (PSS-10). Secondary outcomes include resilience, quality of life (SF-12, EQ-5D-5L), somatic symptoms (SSS-8), dietary habits (REAP-S v.2), psychodynamic structure (OPD-SFK), patient satisfaction, health literacy, and biomarker changes. Discussion This study will provide the first systematic evaluation of a specialized outpatient clinic for Nutritional Psychiatry and Psychosomatics in Europe. Findings will inform the potential of nutrition-focused interventions as part of routine psychiatric and psychosomatic care and may contribute to the development of personalized, integrative treatment strategies. Trial registration ClinicalTrials.gov NCT07050342 This study was prospectively registered at ClinicalTrials.gov (Identifier: NCT07050342), register date: 2025-06-24.